PERENCANAAN JARINGAN SENSOR NIRKABEL DENGAN PEMAKAIAN DAYA TEPAT GUNA - Redaksi Tim Jurnal (Energi & Kelistrikan, 2015)
Wireless Sensor Network is a combination between SCADA (Supervisory Control And Data Acquisition System) system with ad hoc wireless network. This wireless sensor network has already developed very fastly few years lately, because application of wireless sensor network are used in many field. It is necessary to plan for building wireless sensor network precisely so that using energy is not wasted. In this tesis a writer has already survey some aspect on wireless sensor network so that the goal for efficiency energy can be achieved like localization node, time synchronization, modulation, transmit power, size of packet, access medium techniques, network topology and so on. The combination of all the above techniques to plan wireless sensor network that work using a battery give result a wireless sensor network with each node has a capability long life till some years without having replacement for the battery